Informação e ação moral - Pereira, Paulo Henrique Araújo Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this dissertation is to analyze the relationship between information and moral action. Information is understood here as the substrate that can be used by agents to perform moral actions. Moral actions, in turn, express the conduct of human and nonhuman agents in their individual, collective, and environmental relations. The main problems that guide the present reflection can be indicated as follows: (1) What is the relation between information and moral action? (2) Must informational relations necessarily be limited to the domain of reason? (3) What are the advantages and disadvantages of investigating the relation between information and moral action from a non-anthropocentric (but still necessarily anthropomorphic) perspective? To address these problems, we will situate them in the context of Information Ethics, which provides a theoretical basis for the study of ethical issues related to the new technologies of information. Firstly, we provide an overview of the Ethical Information approach that we adopt as a foundation for the Ethical perspective that we intend to elaborate. We then analyze the hypothesis of Ecological Philosophy according to which perception is directly linked to action, independent of abstract representational mediations in the acquisition of information: ecological information is directly perceived by organisms, constituting an essential element in perception/action. Although Ethics is not directly an object of investigation of Ecological Philosophy, we use some of its tenets to investigate the relationship between ecological information and moral action, aiming to highlight the interdependence among moral agency, complexity, and environment. Finally, we present elements that could help with the constitution of an Ecological Informational Ethics approach.

O objetivo desta dissertação é analisar a relação entre informação e ação moral. A informação é aqui entendida como o substrato que pode ser empregado por agentes para desempenhar ações morais. A ação moral, por sua vez, expressa comportamentos de agentes humanos e/ou não humanos em suas relações individuais, coletivas e com o ambiente. Os problemas centrais que direcionam a presente reflexão podem ser assim enunciados: (1) qual é a relação entre informação e ação moral? (2) A relação informacional está necessariamente limitada ao domínio da razão? (3) Quais as vantagens e desvantagens de se investigar a relação entre informação e ação moral a partir de uma perspectiva não-antropocêntrica (ainda que necessariamente antropomórfica)? Para investigar esses problemas, vamos situá-los no contexto da Ética Informacional, que propõe subsídios teóricos para o estudo de temas da Ética relacionados às novas tecnologias da informação. Num primeiro momento, tecemos um panorama geral da abordagem Ética Informacional que adotamos como fundamento para a perspectiva Ética que pretendemos delimitar. A seguir, analisamos a hipótese da Filosofia Ecológica segundo a qual a percepção está diretamente ligada à ação, dispensando mediações representacionais abstratas na captação de informação: a informação ecológica é diretamente percebida pelo organismo e constitui um elemento essencial à percepção/ação. Embora a Ética não seja objeto de investigação da Filosofia Ecológica, analisamos a relação entre informação ecológica e ação moral inspirados em alguns de seus pressupostos com o objetivo de ressaltar a interdependência entre ação, complexidade e ambiente. Por fim, apresentamos elementos que poderiam auxiliar na elaboração de uma abordagem Ética Ecológica Informacional.
Keywords: Ética; Ecologia humana - Filosofia; Agente (Filosofia) Meio ambiente; Teoria da informação; Human ecology Philosophy